2020
DOI: 10.1158/1535-7163.mct-19-0510
|View full text |Cite
|
Sign up to set email alerts
|

Functional miRNA Screening Identifies Wide-ranging Antitumor Properties of miR-3622b-5p and Reveals a New Therapeutic Combination Strategy in Ovarian Tumor Organoids

Abstract: Novel therapeutic strategies are urgently required for the clinical management of chemoresistant ovarian carcinoma, which is the most lethal of the gynecologic malignancies. miRNAs hold promise because they play a critical role in determining the cell phenotype by regulating several hundreds of targets, which could constitute vulnerabilities of cancer cells. A combination of gain-of-function miRNA screening and real-time continuous cell monitoring allows the identification of miRNAs with robust cytotoxic effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…Chen et al developed short duration organoid cultures of multicellular spheroids (MCSs) from ovarian cancer malignant effusions and used them as a platform for empirical drug sensitivity testing [113]. In addition, there are also some preclinical studies that utilized PDOs as a disease model to verify the newly discovered molecular mechanisms and targeting strategies in different subtypes of ovarian cancer [117][118][119][120][121][122].…”
Section: Patient-derived Ovarian Cancer Organoids Overviewmentioning
confidence: 99%
“…Chen et al developed short duration organoid cultures of multicellular spheroids (MCSs) from ovarian cancer malignant effusions and used them as a platform for empirical drug sensitivity testing [113]. In addition, there are also some preclinical studies that utilized PDOs as a disease model to verify the newly discovered molecular mechanisms and targeting strategies in different subtypes of ovarian cancer [117][118][119][120][121][122].…”
Section: Patient-derived Ovarian Cancer Organoids Overviewmentioning
confidence: 99%
“…We postulated that mimicking the effects of a miRNA using drugs already available or easily amenable to clinical practice would constitute a valuable proxy for the clinical use of miRNAs. We previously showed that miR-491-5p [9] and miR-3622b-5p [10] directly target Bcl-xL and EGFR in ovarian cancer cells, and that the combined use of Bcl-xL and EGFR inhibitors, respectively, in clinical trials (ABT-263), which are FDA-approved for the treatment of non-small-cell lung cancer (gefitinib), could efficiently recapitulate the cytotoxicity induced by both of these miRNAs. Although positive, the results of this previous study did bear two drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…But despite numerous still ongoing clinical trials, the current limitations for the clinical use of nucleic acids-such as siRNAs, miRNAs or anti-miRNAs-have undermined such strategies to date [8]. However, understanding the determinants of the cytotoxic phenotype triggered by a given miRNA might enable the identification of druggable targets and thus, the design of innovative therapeutic strategies aiming to mimic its effects [9,10]. Ovarian cancer constitutes the leading cause of death from gynecological malignancies in developed countries, with a low 5-year survival rate of less than 40% [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that miR-3622b-5p augment apoptosis and also sensitizes cells to cisplatin. Therefore, this miRNA can be used for the chemotherapy combined therapeutic approach for the treatment of cancer [111] . Thus, miRNA therapeutics might help counteract drug resistance issues in the near future.…”
Section: Setbacks To Mirna Therapeutics Developmentmentioning
confidence: 99%